Coverage, Usage, Physical Integrity, and Bio-efficacy of Olyset Nets in the Plateau Region, South Benin Following the 2011 Nationwide Distribution. Issue 1 (16th November 2021) - Sovi, Arthur; Gnanguenon, Virgile; Azondekon, Roseric; Oké-Agbo, Frédéric; Houevoessa, Speraud; Salako, Albert S; Akinro, Bruno; Govoetchan, Renaud; Ossé, Razaki; Tokponnon, Filémon; Padonou, Gil G; Akogbéto, Martin C
Abstract: The present study investigated in 8 villages of the Plateau region the coverage, usage, physical integrity, and bio-efficacy of the Olyset nets distributed nationwide by the Benin's National Malaria Control Programme in July 2011. The questionnaire administered as well as the observations made in the households allowed estimating the coverage and usage rates of the 2011 Olyset nets. While their physical integrity was assessed through standard WHO methodology, their bio-efficacy was evaluated through gas chromatography, and WHO cone testing performed with the Kisumu susceptible strain. Mosquito collections through human landing catches (HLCs) were also performed in torn nets to assess if a loss of protection of sleepers occurred as the nets fabric integrity got more damaged. Nine months postdistribution, the coverage and usage rates of the 2011 Olyset nets were 67.4% (95% CI: 65.8–68.9) and 73.3% (95% CI: 70.7–75.8) respectively. About 28% of the 2011 Olyset nets were torn. A drastic drop of the insecticide quantity on the fibers of the nets [from 7.08 µg (95% CI: 5.74–8.42) to 0.2 µg (95% CI: 0.01–0.38)] as well as mortality rates <80% were observed with most nets evaluated. Moreover, the biting rates of An. gambiae s.l. (Diptera: Culicidae) inside torn nets increased in line with their fabric integrity loss. These data support the conclusion that future deployment of nets in the field must be strengthened by community sensitization on their correct use in order to postpone as much as possible appearance of holes and loss of insecticidal activity and encourage repairing of torn nets.